Intraoperative ischemic stroke in elective spine surgery: a retrospective study of incidence and risk - Ishak, Basem; Abdul-Jabbar, Amir; Singla, Amit; Yilmaz, Emre; Glinski, Alexander von; Ramey, Wyatt L.; Blecher, Ronen; Tymchak, Zane; Oskouian, Rod J.; Chapman, Jens R. (Spine, 2020)
Study design: Retrospective study. - Objective: To determine incidence, risk factors, complications, and early postoperative outcome in patients with intraoperative ischemic stroke during elective spine surgery. - Summary of backgraund data: Overall, stroke is the fifth leading cause of death in the United States and the second leading cause of death worldwide. It can be a catastrophic event and the main cause of neurological disability in adults. - Methods: A retrospective review of the electronic medical records of patients who underwent elective spine surgery between January 2016 and November 2018 at a larger tertiary referral center was conducted. Patients with infection and neoplastic disease were excluded. Patient demographics, pre- and postoperative neurological status, surgical treatment, surgical time, blood loss, intraoperative abnormalities, risk factors, history of stroke, medical treatment, diagnostics, hospital stay, complications, and mortality were collected. - Results: Out of 5029 surgically treated patients receiving elective spine surgery, a total of seven patients (0.15%) were identified who developed an ischemic stroke during the surgical procedure. Patients were predominantly females (n=6). Ischemic pontine stroke occurred in two patients. Further distributions of ischemic stroke were: left caudate nucleus, left posterior inferior cerebellar artery, left external capsule, left middle cerebral artery, and acute ischemic supratentorial spots. The main risk factors identified for intraoperative ischemic stroke include hypertension, diabetes, smoking, dyslipidemia, and possibly major intraoperative CSF leak. Three patients (43%) had neurological deficits which did not improve during hospital stay. Two patients recovered fully and two patients died. Therefore, in-hospital mortality rate of this subset of patients was 29%. - Conclusion: With the increase of spinal procedures, it is important to identify patients at risk for having an ischemic stroke and to optimize their comorbidities preoperatively. Patients with intraoperative ischemic stroke carry a higher risk for morbidity and mortality during the index hospitalization. - LEVEL OF EVIDENCE: 4.
Gesehen am 06.08.2020